Effect of Y Concentration on the In Situ Growth Behavior and Corrosion Protection of the MgAlY-LDH Sealing Film on the Anodized Surface of Mg–2Zn–4Y Alloy - Hong, Yuqi; Wu, Liang; Zhang, Xinyi; Zhan, Guoxiang; Chen, Yanning; Yao, Wenhui; Dai, Xu; Wu, Tao; Dai, Xiaowei; Xiang, Jianpeng; Zhou, Yan; Pan, Fusheng (Frontiers in Materials, 2022)
Metal−organic frameworks (MOFs) have shown great potential in gas storage and separation, energy storage and conversion, vapor sensing, and catalysis. Nevertheless, rare attention has been paid to their anticorrosion performances. However, little attention has been paid to them in terms of corrosion and protection. At present, water-stable MOFs, like ZIF-8, have successfully designed and prepared anti-corrosion materials with potential application value. In this study, a graphene oxide (GO)/MgAl-NO3 layer double hydrotalcite (LDHs) coating (G/LDHs coating) was prepared in GO solution using the mixed oxides (Al and Mg) in the MAO coating as endogenous cations by hydrothermal method. On this basis, ZIF-8 particles continuously grow symbiotically on G/LDHs coating (ZG/LDHs coating) using a simple in-situ transformation strategy. ZIF-8 particles with different growth times compensate for the grain boundary defects of the G/LDHs coating precursor buffer layer to different degrees. The polarization test shows that the corrosion current of the ZG/LDHs coating after 25 hours of in-situ growth in situ is 4 orders of magnitude lower than that of the pure MAO coating, demonstrating that MOF materials are ideal materials for constructing high-performance anti-corrosion coatings.